Modified Criterion for Economic Efficiency Estimation of Heat Pumps - Boldyryev, S.; Garev, A.; Ilunin, О.; Shamraev, Anatolij; Selyakov, О.; Leshchenko, O.; Kapustenko, P. O. (The Italian Association of Chemical Engineering, 2013)
In this work the cost-effectiveness of coal mine waste water low potential heat utilization and integration in the enterprise local heating network by the bivalent parallel scheme is investigated. It is shown that the additive criterion of economic efficiency is not always sensitive to the target value because of the reason of non-linear coupling between the arguments of the target function. Several cases were considered from the viewpoint of cost-effectiveness criterion. Moreover, the arguments of the target function are also nonlinear, depending on technological parameters of the heat pump (HP) equipment. As a more effective criteria were proposed the modified canonical additive-multiplicative function and Kolmogorov-Gabor polynomial function to obtain the generalized multivariate estimation of alternatives in two stages procedure.